INDICATIVE ROLE OF VEGETATION IN THE RECLAMATION OF PRECASPIAN ARID LANDSCAPES (THE REPUBLIC OF KALMYKIA) - V. G. Lazareva; V. A. Bananova; Ch. S. Kharitonov; I. A. Goriaev; Nguen Van Dung (Юг России: экология, развитие, 2016)
Aim. The paper studies the influence of water reclamation on vegetation in the central part of the Caspian depression. Findings are necessary for the monitoring studies of natural ecosystems in their modern usage.Methods. The use of key site method and eco-dynamic profiling makes it possible to trace changes in the horizontal structure of vegetation in the coastal and canal areas of the salt lakes. Results. The findings of field research allowed identifying the environmental levels: low, medium, high. Xerophilous species fall out of the phytocenosis composition, while the typical salt-loving plants become widespread, forming endogenous succession of progressive type in a Precaspian desert zone. It aims to desalinize the upper layers of the soil, lower the groundwater and salinity levels. Conclusions. Fluctuation and succession processes can be observed in the central part of the Precaspian depression, the indicator of which is vegetation, its species composition.